The placebo effect in sport: How practitioners can inject words to improve performance - Roelands, B.; Hurst, P. (International Journal of Sports Physiology and Performance, 2020)
Placebo effects involve a complex interplay between an intervention and factors associated with the administration of that intervention, such as expectations, previous experiences, and interactions between participant and researcher.1 (We refer to intervention as any interference aimed at improving or maintaining an athlete`s performance, such as pharmacological/nutritional [eg, caffeine], psychological [eg, imagery], physical [eg, massage], or mechanical [eg, altitude training].) While researchers often regard the placebo effect as a nuisance to control for in randomized control trials, for practitioners (eg, sport scientists, coaches, physiotherapists), it can be a powerful tool to augment the beneficial effects of an intervention.